DIMENSI VERTIKAL WAJAH BERDASARKAN TINGKAT MATURASI TULANG VERTEBRA SERVIKALIS PADA ANAK PERIODE GIGI BERCAMPUR - , drg. IYOP ROPIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cervical vertebral maturation associated with skeletal bone maturation, including facial bones. The rate of bone maturation cervical vertebrae (CVMS) can be used as an indicator of the growth of the facial bones. The purpose of this study to determine the vertical dimension of the face based on the level of the cervical vertebral maturation in children teeth mixed period. Observational study with cross sectional approach conducted on 35 boys and 32 girls, aged 6-12tahun patient clinic of the Hospital Pediatric Dentistry Prof Soedomo, FKG UGM. Measurement of anterior facial vertical height (N-Me, N-ANS, ANS-Me) and posterior face (S-Go). Assessment of the level of the cervical vertebral maturation method Hassel and Farman with cephalometric approach. Data analysis was done by unpaired t test, ANOVA test to distinguish between one path CVMS and Spearman correlation test Research results between boys and girls showed a significant difference (p <0.05) mean N-Me, ANS-Me, S-Go at CVMS 1.2 and 3 Size faces N-Me, N-ANS, ANS-Me and S-Go between CVMS boys showed differences (p <0.05), while girls face on the size of N-Me and S-Go. Correlation coefficient boys showed a strong relationship between CVMS with N-Me and N-ANS (r = 0.812